Hello,

I have the following equation with two unknowns and I can't seem to solve it.

0.5 = 3.5m + 3d

I made 2 equations (one for each unknown)

Equation for m:

m = (0.5 - 3d)/3.5

Equation for d:

d = (0.5 - 3.5)/3

First, I tried solving for d by substituting m in original equation as:

0.5 = 3.5(m) + 3d

so equation becomes:

0.5 = 3.5( (0.5 - 3d) /3.5) + 3d

0.5 - 3d = 3.5( (0.5 - 3d) /3.5)

0.5 - 3d = 3.5(0.5/3.5 - 3d/3.5)

0.5 - 3d = 3.5(0.5/3.5) - 10.5d/3.5

0.5 - 3d = 0.5 - 10.5d/3.5

0.5 + 0.5 - 3d = 10.5d/3.5

1-3d = 10.5d/3.5

3.5(1-3d) = 10.5d

3.5 - 10.5d = 10.5d

3.5 = 21d

3.5/21 = d

d = 0.166666666 ????

I believe "d" is supposed to equal 1.45 !